Evaluating Abdominal Obesity by Waist Circumference, Anthropometric Indices and Bioelectrical Impedance Analysis: A Comparative Pilot Study - Anastasiia Nahorna; Heiner Baur (Obesity Science & Practice)
ABSTRACT Introduction Abdominal obesity significantly increases the risk of various health conditions, making accurate assessment crucial for diagnosis and treatment. This study compares the effectiveness of anthropometric methods and conventional bioelectrical impedance analysis in evaluating abdominal obesity. Materials and Methods Twenty adults (10 males, 10 females; age 45 ± 11.4 years; height 170 ± 8.63 cm; body weight 91.3 ± 19.2 kg; BMI 31.7 ± 5.31 kg/m2) participated in a single‐visit pilot study at the Bern Movement Lab at Bern University of Applied Sciences. Anthropometric measurements; including body weight, height, waist and hip circumferences; anthropometric indices; including BMI, waist‐to‐hip ratio, waist‐to‐height ratio and conventional bioelectrical impedance analysis were collected. Spearman's Rank Correlation was used for statistical analysis due to non‐normal data distribution. Results Waist circumference, waist‐to‐hip ratio, and waist‐to‐height ratio consistently classified all participants as having abdominal obesity. In contrast, bioelectrical impedance analysis identified fewer cases, with only 40% of men and 10% of women classified as having abdominal obesity. Strong correlations were observed between waist circumference, waist‐to‐height ratio, and visceral fat, whereas waist‐to‐hip ratio showed weaker correlations. Conclusions Simple anthropometric methods such as waist circumference, waist‐to‐hip ratio, and waist‐to‐height ratio are useful for evaluating abdominal obesity, with waist‐to‐height ratio often considered a more reliable predictor of central obesity. However, bioelectrical impedance analysis shows inconsistencies, and the waist‐to‐height ratio should be considered as a standard metric in future guidelines. Large‐scale multiethnic studies are recommended to validate these findings.